Improving the process of zoning in a community mental health team. Issue 1 (4th February 2020) - Adams, Alexander; Perry, Jennifer; Young, Stephanie
Abstract : Introduction: A zoning system is used to ensure that service users receive appropriate levels of support while they are using community mental health team (CMHT) services. Patients are split into red, amber and green zones and are discussed in a daily morning meeting to ensure management plans are in place. We identified that the meeting was an area for improvement as initial feedback indicated that the meeting was repetitive, newcomers to the team found that they did not understand why patients were in different zones and discussions were not being documented. Our three aims for the project were to improve staff-rated satisfaction by 25%, to improve weekly documentation of discussions to 100% and to improve the quality of information handed over by 25% over 4 months. Methods: We used the Model for Improvement and "plan, do, study, act" (PDSA) cycles to test change ideas such as having someone chair the meeting, use of a 'situation, background, assessment, recommendation, decision' (SBARD) format to handover, introduction of a blue zone for inpatients and documentation in a specific part of the electronic notes at a specific time. Results: We did not find our PDSA cycles led to a consistent change in satisfaction, quality and efficiency. We found an improvement of SBARD use up to 100% although this was not always consistent and an improvement in documentation to 100% for 3 weeks however this was not sustained. Conclusion: On examining barriers to change, we found the key to sustaining improvement is in ensuring multidisciplinary team member involvement at all stages of the Quality Improvement project.